Role of Islamic Microfinance Institutions for sustainable development goals in Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Kassim, Salina; Che Embi, Nor Azizan; Md Saad, Norma (2020)
The goal of this paper is to explore the Islamic Microfinance Instruments (IMFs) in attaining sustainable development goals (SDGs) in Bangladesh. Propose a conceptual model along with exploring the efforts in attaining SDGs to fill the gap. The methodology of the study predicated on secondary data includes existing relevant literature, books and annual reports of easily sampled IMFs and Microcredit Regulatory Authority (MRA) in Bangladesh. The findings of the research show that microfinance organisations have a broader range to attain Sustainable Development Goals through their various investment modes. The analysis categorises the microfinance tools into large parts that are poverty decrease, end hunger for food, good health, equality education, clean drinking water, sanitation energy, gender equality, empowering women, and funding which have an optimistic effect to the real sector of the sustainable economic climate that will lead towards attaining SDGs. Microfinance organisations are carrying on their initiatives in attaining sustainable development goals through their various products. With growing the potentiality, microfinance has both direct and indirect effects on ensuring financial development, environmental sustainability, and social inclusion by creating work opportunity, distributing knowledge and skills, making self-dependent, protecting from undesirable effects. The paper also attempts to put suggestions to lessen the difficulties of microfinance performing as impediments to achieving the SDGs.